Validating Alzheimer's disease micro RNAs using next-generation sequencing - Keller, Andreas; Backes, Christina; Haas, Jan; Leidinger, Petra; Maetzler, Walter; Deuschle, Christian; Berg, Daniela; Ruschil, Christoph; Galata, Valentina; Ruprecht, Klemens; Stähler, Cord; Würstle, Maximilian; et al. (Alzheimer's and dementia, 2016)
Abstract Introduction Molecular biomarkers for Alzheimer's disease (AD) can support detection and improved care for patients, but novel candidates require verification. We previously reported a 12-micro RNA (miRNA) blood-based signature using next-generation sequencing (NGS) of 54 AD cases and 22 controls. Methods We performed validation of 49 AD cases and 55 controls using NGS and also included 20 mild cognitive impairment and 90 multiple sclerosis samples to identify nonspecific markers. Thus, 103 AD cases, 77 unaffected controls, and 110 diseased controls were sequenced. Although the initial cohort came predominantly from the United States, the validation samples were collected in Germany. Results Five hundred eighty miRNAs were detected in the blood. In the initial cohort, we observed 203, in the validation cohort, 146 dysregulated miRNAs at a significance level of 0.05. With 68 miRNAs, the overlap was significant (P = .0003). Likewise, the area under the receiver operator characteristic curve values of the miRNAs correlated (correlation of 0.93; 95% confidence interval 0.89?0.96; P <10?16). Discussion MiRNAs have the potential to support AD diagnosis and patient care.
Gesehen am 11.05.2020